Resposta neuromuscular a protocolos de treinamento com número máximo de repetições e diferentes durações das ações musculares - Sandra Carvalho Machado (2012)
The training protocols designed to improve muscle strength may be prescribed with maximum number of repetitions (MNR) per set aiming to increase the number of motor units activated. However, some studies have shown that other training variables may influence the MNR and electromyographic activity. Therefore, the aim of this study was to compare the maximum number of repetitions and the electromyographic signal amplitude among sets and between training protocols with different durations of muscle actions and the same duration of repetition. Nineteen male volunteers with at least six months in strength training took part in this study. In the experimental sessions 1 and 2 subjects performed tests of one repetition maximum (1RM) in the Smith machine bench press. In the experimental sessions 3 and 4, two training protocols were performed in the Smith machine bench press, characterized by three sets of the maximal number of repetitions at 60% of one repetition maximum (1RM) and three minutes of rest interval among sets. One of the protocols was performed using concentric muscle actions of 2s and eccentric muscle actions of 4s (2-4 protocol) and the other one with concentric muscle actions of 4s and eccentric muscle actions of 2s (4-2 protocol). The protocols were randomly and balanced assigned over the experimental sessions. The electromyographic signal amplitude of each repetition to the muscles pectoralis major and triceps was quantified by the integral of the normalized electromyographic signal (iEMGN) obtained by the average of repetitions performed in each set of the training protocols. Subjects performed fewer repetitions in 4-2 protocol than in 2-4 protocol. The pectoralis major showed higher iEMGN in 4-2 protocol and triceps showed no difference between the protocols. In both protocols, there was a reduction in the number of repetitions and increased iEMGN along sets. The present study showed that greater muscle activation can be obtained even when a smaller number of repetitions are performed. In addition, the two studied muscles showed different behaviors in response to the same training protocols.